Audio visual Sebagai Layanan Bimbingan Belajar Terhadap Perkembangan Bahasa Anak Usia Dini - Romlah, Romlah; Defriyanto, Defriyanto (Universitas Islam Negeri Raden Intan Lampung, 2018)
Language development must be given since children are early, because language is one aspect that must be developed in early childhood education. Children are directed to be able to use and express their thoughts by using the right words so that children's language skills can develop optimally. The purpose of this study is to find out the language skills of early childhood through tutoring services with audio visual media. The population of this study was the sun class students at Al Rizky Bandar Lampung PAUD with a sample of n = 20 students taken randomly. There is language development in early childhood after conducting tutoring services with audio visual media. Tutoring services with audio visual media can develop early childhood language.